Cardio-Respiratory and Metabolic Implication of Intranasal Packing in Patients Undergoing Sino-Nasal Surgery - Sheikh, Nadeem Ahmed; Anwar, Wasif; Khan, Yasser Saeed; Siddiqi, Fuad Ahmad; Hayat, Asma; Nadeem, Kanwal (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine impact of various forms of intra nasal packings and trans-septal suturing (without nasal packing) on cardiopulmonary and metabolic milieu of patients undergoing nasal and paranasal sinus operations. Study Design: Randomized controlled trial. ( Ltr no: IERB-01/3/23/Trg dated 8 March 2023)Place and Duration of Study: Department of Otorhinolaryngology (ENT), Combined Military Hospital, Jhelum Cantonment, Pakistan, from Aug 2022 to Aug 2023.Methodology: Clinical and laboratory markers of cardio-pulmonary and metabolic assessment of 140 subjects were evaluated, who had undergone some form of intranasal packing procedure or trans-septal suturing (without nasal packing) following nose or paranasal sinus operations. Results: Ventilated nasal packs and completely avoiding nasal packing by performing trans-septal suturing have a significant impact on clinical parameters like resting heart rate, respiration, blood pressure, arterial blood pH and arterial blood partial pressure of carbon dioxide (PaCO2) in patients undergoing surgical operations of the nose and paranasal sinuses.Conclusion: We strongly recommend adopting less invasive and technically more advanced operative methodology and refining surgical expertise regarding septal splinting during rhinologic operative procedures, mitigating discomfort and antecedent morbidity in patients undergoing these sino-nasal surgical operations.